HEADMASTER AS A CHANGE AGENT IN REALIZING THE VISION OF A SUPERIOR SCHOOL - Edi Suhariyono (Indonesian Journal of Education (INJOE), 2023)
This study aimed to analyze the role of the head of the school as an agent of change in realizing the vision of an excellent school. The research explored the vital characteristics of school leaders and examined the implementation steps to understand how the head of the school positively influenced change within the school. The findings revealed that a director of the school with visionary LeadershipLeadership, practical communication skills, high integrity, and the ability to build strong relationships played a central role in realizing the vision of an excellent school. The implementation steps included effective communication, forming a change team, identifying change needs and opportunities, active participation of stakeholders, providing training and development, and regular monitoring and evaluating change progress. These steps were crucial factors in achieving the objectives of the school's vision for excellence. In conclusion, the head of the school played a critical role as an agent of change. By possessing the qualities above and actively engaging in the implementation process, they inspired and empowered the school community to create a collaborative and supportive environment for positive change. Regular monitoring and evaluation ensured continuous growth and development. Therefore, the head of the school needs to possess strong leadership qualities and actively involve all stakeholders in pursuing the school's vision. Their actions and efforts influenced the school's success, enabling the desired outcomes